GAMBARAN PYSCHOLOGICAL WELL BEING PADA LANSIA YANG BERSTATUS JANDA - Nikita Cestin Nalle; Christiana Hari Soetjiningsih (PSIKOLOGI KONSELING, 2020)
The purpose of this research is to know psychological well-being to the widowed elderly after their husbands’ death and what the factors that influence the widowed elderly when their husbands’ death. This research is done to the widowed elderly by using phenomenological qualitative approach. Interpretative phenomenological analysis (IPA) is used of the data analysis. This research was successful to identify the psychological well-being. Both of the participants were able to accept their condition as widowed elderly and overcome their bad experiences in the past by getting social support from their children, joining positive activities outside of their houses, and building a good relationship with God. The next researchers who are interested to do a research about psychological well-being to the widowed elderly can research the causes of divorce or another condition.Keywords : Widowed Elderly; Husbands’ Death; Psychological Well-Being; Social Support; Relationship with God